Bright Green Emission of Tb 3+ Doped Lithium Sodium Potassium Borate Glasses for Photonic Application - N. Jarucha; Y. Ruangtaweep; P. Meejitpaisan; Paisan Kanthang; N. Wongdamnern; P. Limsuwan; H. J. Kim; J. Kaewkhao; Thanapong Sareein (Integrated ferroelectrics, 2023)
AbstractThe melt-quenching approach was implemented to create terbium-doped lithium sodium potassium borate glasses (LNKBTb). Archimedes' principle, absorption and luminescence spectra, including CIE chromaticity were used to characterize the properties of glasses. Terbium in glasses absorbs photon in the visible and near infrared ranges. The intense green emission at 544 nm was generated by the terbium 5D4 to 7F5 transition when excited with ultraviolet–visible (UV–Vis) light. The emission intensities of LNKBTb glasses increased with increasing terbium concentrations up to 4 mol%, after which they decreased, resulting in the concentration quenching effect, whereas decay time decreases as Tb2O3 content increases. In CIE 1931, the overall color of emission is green. May bring can continue to develop to use as a photonic material in green light sources and lasers.Keywords: Borate glassesCIEluminescenceterbium AcknowledgmentsThe authors would like to thank all graduate students and co-researchers in the research laboratory of the Center of Excellence in Glass Technology and Materials Science, and there is also the Industrial Materials Science Division Faculty of Science and Technology Rajamangala University of Technology Phra Nakhon.Disclosure StatementNo potential conflict of interest was reported by the author(s).Additional informationFundingThis project is funded by the National Research Council of Thailand (NRCT) (Contract No. N41A650404) and CERNTEK COMPANY LIMITED.
Keywords: Glass properties and applications; Luminescence Properties of Advanced Materials; Photorefractive and Nonlinear Optics